The appropriate measures in developing IDLE waqf land - Syed Abdul Kader, Sharifah Zubaidah (2016)
Waqf land is land that has been endowed by the owner of land as waqf for a specific pupose or for general use , benefits of which would accrue to a specific group of persons or the public at large. Whether a waqf is to be considered as a special waqf or a general waqf depends on the intention of the donor as expressed in the instrument creating the waqf (‘waqfiyyah’ or waqf declaration).